1999
DOI: 10.1051/forest:19990504
|View full text |Cite
|
Sign up to set email alerts
|

The effect of desiccation and rough-handling on the survival and early growth of ash, beech, birch and oak seedlings

Abstract: -Fraxinus excelsior L., Fagus sylvatica L., Betula pendula Roth. and Quercus robur L. seedlings were grown for 1 year with or without an undercutting treatment in July of their first growing season. In the following March, seedlings were lifted from the nursery and subjected to 0, 12 or 36 h desiccation followed by 0 or 10 drops from 1 m. Morphological measurements, moisture content and root electrolyte leakage were determined. Field performance was measured after 1 year. The effects of undercutting, roughhand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…For the shoot the water content is higher in the European beech, while for the root it is higher in Norway spruce. These results confi rm the data of McKay et al (1999) which show that in seedlings of many species -such as beech and some Picea species -the water content in the root system is inversely proportional to the tree dia meter. Water content of the saplings is lower than that of seedlings for both species: Norway spruce 79.7% (above-ground component) and 76.9% (below-ground component), European beech 90.0% (aboveground component) and 110.3% (belowground component).…”
Section: Water Contentsupporting
confidence: 80%
“…For the shoot the water content is higher in the European beech, while for the root it is higher in Norway spruce. These results confi rm the data of McKay et al (1999) which show that in seedlings of many species -such as beech and some Picea species -the water content in the root system is inversely proportional to the tree dia meter. Water content of the saplings is lower than that of seedlings for both species: Norway spruce 79.7% (above-ground component) and 76.9% (below-ground component), European beech 90.0% (aboveground component) and 110.3% (belowground component).…”
Section: Water Contentsupporting
confidence: 80%
“…to examine seasonal variation in stress resistance in response to heat treatments applied in vitro. Past studies have identified relationships between fine root EL and seedling physiological quality or field performance potential in various hardwood species (e.g., McKay et al, 1999;Garriou et al, 2000), though O'Reilly et al (2002) reported no correlation with height growth in freshly lifted or cold stored ash and maple. As in our study, sampling EL of stem (Deans et al, 1995;Sarvaš, 2001) and root collar tissues (Schute and Sarvaš, 1999) has also proved useful in evaluating seedling physiological activity of hardwood species.…”
Section: Cold Hardiness Developmentmentioning
confidence: 99%
“…For hardwoods, relatively little information is available. Most hardwood EL research in the past was performed using roots of European species (Edwards, 1998;McKay et al, 1999;O'Reilly et al, 2003). Many important hardwood species of eastern North America, including black walnut, have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the greater the value of seedlings, the larger is the ratio between the mass of the root system and the mass of the above-ground part. McKay et al (1999) showed that the survival rate of pruned seedlings of beech in the cultivation is higher compared to seedlings that were not pruned.…”
Section: Introductionmentioning
confidence: 99%